Refining Child Pornography Law - Hessick, Carissa Byrne (University of Michigan Press, 2016)
The legal definition of child pornography is, at best, unclear. In part because of this ambiguity and in part because of the nature of the crime itself, the prosecution and sentencing of perpetrators, the protection of and restitution for victims, and the means for preventing repeat offenses are deeply controversial. In Refining Child Pornography Law, experts in law, sociology, and social work examine child pornography law and its consequences in an effort to clarify the questions and begin to formulate answers. Focusing on the roles of language and crime definition, the contributors discuss the increasing visibility child pornography plays in the national conversation about child safety, and present a range of views regarding the punishment of those who produce, distribute, and possess materials that may be considered child pornography.